(untitled) (Itinera, 2025)
This essay takes its cue from the collective volume Foucault’s Aesthetics of Existence and Shusterman’s Somaesthetics. Ethics, Politics, and the Art of Living (eds. Valentina Antoniol and Stefano Marino, Bloomsbury Academic, 2024) is a timely and ambitious work that discusses two major philosophical approaches to the body and subjectivity. While the book’s essays explore the intersections and tensions between the aesthetics of existence and somaesthetics—highlighting their shared concern with embodied practices of self-formation, ethical transformation, and resistance to normative power structures—my reading gradually turned into an extended reflection on the notion of the Bio-Soma that emerges from these dialogues. The collection explores the intersections and tensions between aesthetics of existence and somaesthetics, highlighting their shared concern with embodied practices of self-formation, ethical transformation, and resistance to normative power structures. Through a rich and well-structured set of contributions, the volume maps the body as a critical medium, political agent, and aesthetic space of creativity and reciprocity. Contemporary debates on the ethics and politics of embodied subjectivity are relevant for rethinking the relationship between bio- and soma-power today.